HPLC-ESI-MS/MS validation and pharmacokinetics of kalopanaxsaponin A in rats1. Issue 10 (6th February 2015) - Qiu, Feng; Zhao, Xiaoping; Lu, Xuran; Wang, Manyuan; Gong, Muxin
<x xml:space="preserve">Abstract</x> A new LC-MS/MS method was developed and validated for the analysis of kalopanaxsaponin A in rat plasma.